Variabel Yang Memengaruhi Risiko Investasi Saham Pada Perusahaan Farmasi di Bursa Efek Indonesia - Simamora, Helena Oktaviana; Wiksuana, I Gusti Bagus (E-Jurnal Manajemen; Vol 3 No 12 (2014), 2014)
The purpose of this study was to determine the effect of inflation, interest on deposits, the exchange rate against USD, capital structure, operating leverage, financial leverage, and liquidity of the company against the risk of stock investments in pharmaceutical companies in Indonesia Stock Exchange 2009-2013. This study used a non-participant observation method is to learn and see the published financial statements of pharmaceutical companies that went public on the official website of the Stock Exchange (www.idx.co.id), used a sample of 7 companies were taken by purposive sampling method and the data processed using multiple linear regression analysis techniques. The results of this study indicate that the company's capital structure and liquidity are positive and significant effect on the risk of stock investing, operating leverage is not positive and significant effect on the risk of stock investments, and inflation, interest on deposits, the exchange rate against USD and financial leverage partially negative effect and significant impact on the risk of stock investments in pharmaceutical companies in BEI 2009-2013.
Keywords: Faktor makro, Faktor mikro, Risiko investasi saham